2015
DOI: 10.15252/embj.201591118
|View full text |Cite
|
Sign up to set email alerts
|

The balance of Id3 and E47 determines neural stem/precursor cell differentiation into astrocytes

Abstract: Adult neural stem/precursor cells (NSPCs) of the subventricular zone (SVZ) are an endogenous source for neuronal replacement in CNS disease. However, adult neurogenesis is compromised after brain injury in favor of a glial cell fate, which is mainly attributed to changes in the NSPC environment. Yet, it is unknown how this unfavorable extracellular environment translates into a transcriptional program altering NSPC differentiation. Here, we show that genetic depletion of the transcriptional regulator Id3 decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 71 publications
7
55
0
1
Order By: Relevance
“…In addition, we found that overexpression of E47 could inhibit Wnt signaling by luciferase reporter assay. Consistent with a previous study, we confirmed that ID3 could bind to E47, and we found that overexpression of ID3 inhibited the binding ability of E47 to the β‐catenin promoter region and induced β‐catenin expression in cholangiocarcinoma cells. Therefore, we provided evidence that ID3 interacts with E47 and induced transcriptional induction of β‐catenin.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we found that overexpression of E47 could inhibit Wnt signaling by luciferase reporter assay. Consistent with a previous study, we confirmed that ID3 could bind to E47, and we found that overexpression of ID3 inhibited the binding ability of E47 to the β‐catenin promoter region and induced β‐catenin expression in cholangiocarcinoma cells. Therefore, we provided evidence that ID3 interacts with E47 and induced transcriptional induction of β‐catenin.…”
Section: Discussionsupporting
confidence: 92%
“…According to the JASPAR CORE database, we found E47 to be a bHLH transcription repressor that could directly bind to the promoter region of β‐catenin. Several studies also showed that E47 can repress the transcription of certain genes by binding to their promoter regions . Furthermore, Zhao et al demonstrated that E47 could down‐regulate the level of β‐catenin in colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the E-protein antagonist Id3 orchestrates BMP2-induced astrocyte differentiation (Pfurr et al 2017). Upon cortical brain injury, Id3 is induced by BMP2 to neutralize E47 activity and promote astrocyte differentiation (Bohrer et al 2015). The E2A proteins also function as tumor suppressors and are associated with a wide variety of chromosomal translocations associated with childhood leukemias (Bain et al 1997;Aspland et al 2001).…”
Section: E Proteinsmentioning
confidence: 99%
“…The replacement text is: "Another important aspect of our study is our finding that TCF3 AS is regulated during hESC differentiation by hnRNP H/F. TCF3 is known to play important roles in a variety of differentiation-related processes, such as hematopoietic and neuronal development (Semerad et al 2009;Bohrer et al 2015). Moreover, it also has been reported recently that TCF3 coordinates early heart formation by functioning with other HLH and ID proteins (Cunningham et al 2017).…”
mentioning
confidence: 71%
“…For example, TCF3 maintains the hematopoietic stem cell pool and promotes maturation of myelolymphoid and myeloerythroid progenitors (Semerad et al 2009). TCF3 is also involved in controlling differentiation of neural stem cell into astrocytes (Bohrer et al 2015). These reports imply that TCF3 functions to control either stem cell self-renewal or differentiation."…”
mentioning
confidence: 99%